EP938 Plasmajet In ovarian cancer surgery. (1st November 2019) - Natarajan, P; Macdonald, R; Decruze, B
Abstract : Introduction/Background: Ovarian cancer is the second most commonest gynaecological cancer but the leading cause of mortality among the gynaecological cancers. The primary treatment is surgery and adjuvant chemotherapy which is possible in early stage cancers. In advanced stage cancers primary treatment is associated with increased morbidity and mortality. Neoadjuvant chemotherapy with primary chemotherapy and interval debulking surgery as similar outcome to primary surgery with fewer complications.Optimal cytoreduction is associated with improved prognosis however it may be at the expense of stoma, spelenectomy, peritoneal stripping and other extensive surgeries. Plasmajet is an energy device using plasma and reduce the extensive surgery avoding its complications whilst retaining Outcome. There are no studies looking at correlation between clinical findings and Histological findings after treatment with plasmajet. in this study we looked hitological details of the peritonuem after treatment with Plasmajet. Methodology: This is a prospective conducted in LWH in Liverpool UK where in the recruitment began in January 2019. In women who were diagnosed to have stage 3 or 4 Ovarian cancer are eligible for Plasmajet study. A 2 × 2 cm involved peritonuem is excised during surgery either at primary or interval debulking surgery. The specimen is sent to the Gynaecological Pathologist. Tumour depth involvement, plasmajet penetration, Viable tumour and damage to other structures are also noted Results: 10 cases have been recruited until May 2019. 2 cases did not have tumour and the plasmajet penitration was good and no futher damage was seen. In 2 cases the penteration of Plasmajet and disease on the peritonem was the same and in 2 cases plasmajet depth was more. In 4 cases the depth of disease involvement was more than the plasmajet spread. Conclusion: Plasmajet may be used in surgical excision whilst ablation may be not effective. Disclosure: Nothing to disclose.